The Brexit deterrent? How member state exit shapes public support for the European Union. (March 2022) - Hobolt, Sara B; Popa, Sebastian Adrian; Van der Brug, Wouter; Schmitt, Hermann
What are the effects on public support for the European Union (EU) when a member state exits? We examine this question in the context of Britain's momentous decision to leave the EU. Combining analyses of the European Election Study 2019 and a unique survey-embedded experiment conducted in all member states, we analyse the effect of Brexit on support for membership among citizens in the EU-27. The experimental evidence shows that while information about the negative economic consequences of Brexit had no significant effect, positive information about Britain's sovereignty significantly increased optimism about leaving the EU. Our findings suggest that Brexit acts as a benchmark for citizens' evaluations of EU membership across EU-27, and that it may not continue to act as a deterrent in the future.